Matija Murko’s Research on the South Slavic Epic Tradition and Czechoslovakian Slavistics - Fischerová, Sylva (Primerjalna književnost, 2025)
This paper, devoted to Matija Murko’s research on the South Slavic epic tradition, focuses primarily on relationships and facts hitherto unknown or only partially known. These include, for example, the role of Gilbert Murray and the Berlin conference of 1908 as an important impulse for Murko’s further research, the fate of the wax cylinders from Murko’s trips in the 1930s, and the Czech typescript of his Cesty za národní epikou srbsko-charvátskou v letech 1930–1932 (published in 1951 in translation as Tragom srpsko-hrvatske narodne epike: putovanja u godinama 1930–1932). It also brings to light previously unpublished documents: the testimony of the diary of Murko’s wife from their stay in Paris in 1928; the article from Borba, “Američki učenjak o jugoslavenskim narodnim pjesmama,” which suggests that, probably toward the end of his life, Murko acknowledged that extensive research had been conducted by other explorers in the field of the South Slavic epic tradition in the Balkans as well. There is also the problematic testimony from the archives of the Czechoslovak secret police, introducing Roman Jakobson as having attended Murko’s lectures after his arrival in Prague (as a part of Soviet mission) in 1920. The inspiring and amicable milieu of interwar Prague is also presented, as well as Murko’s cooperation with major figures in Czech Slavistics. Just as important, however, is what did not happen—such as a meeting between Murko and Avdo Međedović in Bijelo Polje in 1924, or an unpublished book of Murko’s works in English translation, planned by J. M. Foley.
Keywords: comparative literature; Czech Slavic studies; češka slavistika; epika; južnoslovanske književnosti; ljudsko slovstvo; Murko, Matija; oral tradition; Primerjalna književnost; Slavistika; Slovenian literary historians; slovenski literarni zgodovinarji; South Slavic epic poetry; South Slavic literatures; teorija ustnosti